Mortality Associated with Influenza in Tropics, State of São Paulo, Brazil, from 2002 to 2011: The Pre-Pandemic, Pandemic, and Post-Pandemic Periods. (12th June 2013) - Freitas, André Ricardo Ribas; Francisco, Priscila M. S. Bergamo; Donalisio, Maria Rita
Abstract : The impact of the seasonal influenza and 2009 AH1N1 pandemic influenza on mortality is not yet completely understood, particularly in tropical and subtropical countries. The trends of influenza related mortality rate in different age groups and different outcomes on a area in tropical and subtropical climate with more than 41 million people (State of São Paulo, Brazil), were studied from 2002 to 2011 were studied. Serfling-type regression analysis was performed using weekly mortality registries and virological data obtained from sentinel surveillance. The prepandemic years presented a well-defined seasonality during winter and a clear relationship between activity of AH3N2 and increase of mortality in all ages, especially in individuals older than 60 years. The mortality due to pneumonia and influenza and respiratory causes associated with 2009 pandemic influenza in the age groups 0–4 years and older than 60 was lower than the previous years. Among people aged 5–19 and 20–59 years the mortality was 2.6 and 4.4 times higher than that in previous periods, respectively. The mortality in all ages was higher than the average of the previous years but was equal mortality in epidemics of AH3N2. The 2009 pandemic influenza mortality showed significant differences compared to other years, especially considering the age groups most affected.